Exploring the landscape of developmental and epileptic encephalopathies and gene research global dynamics via bibliometric study 2001–2025 - Liu, Wen-hui; Zhang, Si-qi; Ding, Yan; Zhao, Ying; Meng, Heng (Frontiers in Neurology, 2025)
Objective (background)The aim of this study is to analyze the current research status and future prospects of the field of developmental and epileptic encephalopathy (DEE) and gene through bibliometric methods. It aims to explore the trends and potential developments in this field.MethodsA systematic search of the DEE and gene literature from 2001 to 2025.2 was conducted using the Web of Science core collection database. Supplementary PubMed searches for this field’s clinical research trends ensured verified data comprehensiveness and methodological rigor. Quantitative analysis of co-authorship networks was performed using VOSviewer and CiteSpace tools.ResultsA total of 1,022 articles related to the field of DEE and gene were included in this study, authored by 8,355 researchers affiliated with 7,238 institutions across 315 countries. United States emerged as the leading research countries in this field, with the National Institute of Health and Medical Research. Professor Ingrid Scheffer had the highest number of publications in this field, and the journal Epilepsy had the highest citation count. The research hotspots in this field revolved around epilepsy, mutations, epileptic encephalopathy, de novo mutations, and seizure.ConclusionThe research on DEE and gene is currently experiencing rapid growth. The field is expanding, and the research is becoming more in-depth.